Direct Antenna Modulator for m-QAM Applications - Ford, Kenneth L.; Henthorn, Stephen; O'Farrell, Tim (2020 14th European Conference on Antennas and Propagation (EuCAP), 2020)
This paper introduces a concept for direct antenna modulation using a metasurface based antenna. The antenna can be controlled with the use of an external bias to control both the amplitude and phase of the transmitted signal, in a continuous way, to provide m-QAM direct antenna modulation. The DAM comprises of five metasurfaces, four of which control the transmitted phase through the use of a varactor diode, and the fifth uses a PIN diode to control the transmitted phase. Numerical simulations are presented which show that the transmitted phase can be varied over a 360° range with a amplitude dynamic range of 25dB.